Neoadjuvant denosumab: its role and results in operable cases of giant cell tumour of bone. (February 2019) - Puri, A.; Gulia, A.; Hegde, P.; Verma, V.; Rekhi, B.
Abstract : Aims: The aims of this study were to evaluate the efficacy of preoperative denosumab in achieving prospectively decided intention of therapy in operable giant cell tumour of bone (GCTB) patients, and to document local recurrence-free survival (LRFS). Patients and Methods: A total of 44 patients received preoperative denosumab: 22 to facilitate curettage, 16 to facilitate resection, and six with intent of converting resection to curettage. There were 26 male and 18 female patients. The mean age was 27 years (13 to 47). Results: The mean number of denosumab treatments was five (2 to 7) per patient. In 42 of 44 patients (95%), denosumab helped to achieve prospectively decided intention. A total of 41 patients were available for follow-up at a mean follow-up of 34 months (24 to 48). There were 12 local recurrences (29%), in 11 patients (11/25, 44%) who had curettage and in one patient (1/16, 6%) who had resection. The mean time to local recurrence was 16 months (8 to 25). The LRFS was 76% at two years: 94% for cases with resection and 64% for cases with curettage (p = 0.013). Conclusion: Although local control rates are unlikely to improve with use of preoperative denosumab, a short preoperative course of denosumab can facilitate surgery in certain cases of operable GCTB, with a high risk of local recurrence making curettage or resection technically easier. It may also help in converting a lesion requiring resection to a lesion that could possibly be treated with curettage.